2004
DOI: 10.1099/vir.0.79797-0
|View full text |Cite
|
Sign up to set email alerts
|

Shift in Japanese encephalitis virus (JEV) genotype circulating in northern Vietnam: implications for frequent introductions of JEV from Southeast Asia to East Asia

Abstract: This study analyses the evolutionary relatedness of 16 Japanese encephalitis virus (JEV) isolates (nine from Vietnam and seven from Japan) to previously published JEV strains using E gene sequence data. Vietnamese and Japanese strains isolated between 1986 and 1990 were found to cluster in genotype 3. However, more recent Vietnamese and Japanese strains isolated between 1995 and 2002 grouped within genotype 1, now a dominant though previously unreported genotype in Vietnam. In addition, in this study, strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
117
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 30 publications
7
117
0
1
Order By: Relevance
“…mosquitoes, from genotype III to genotype I, was witnessed in East Asia during the 1990s (11,12). These results and phylogenetic analysis of old JEV strains in Japan and Southeast Asia (11) strongly suggested that JEV could be transferred frequently from Southeast Asia to East Asia.…”
Section: Discussionmentioning
confidence: 62%
“…mosquitoes, from genotype III to genotype I, was witnessed in East Asia during the 1990s (11,12). These results and phylogenetic analysis of old JEV strains in Japan and Southeast Asia (11) strongly suggested that JEV could be transferred frequently from Southeast Asia to East Asia.…”
Section: Discussionmentioning
confidence: 62%
“…Although the vaccination history of the patients with aseptic meningitis was unknown, the data suggest that the risk of JEV infection is still a matter of concern. The predominant JEV genotype that shifted from Type III to Type I in Japan may have been causing the change of clinical symptoms associated with JE from encephalitis to meningitis (17). Assessment of JE infection risk is quite complicated as described earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, genotype I, which is genetically close to those from Malaysia, was found to have been introduced and co-circulated with and/or ultimately replaced the existing genotype III in many Asian countries (Fulmali et al, 2011;Huang et al, 2010;Ma et al, 2003;Nga et al, 2004;Pyke et al, 2001;Wang et al, 2007;Yoshida et al, 2005;Yun et al, 2010). Putatively, the introduced genotype I originated from Southeast Asia (Nabeshima et al, 2009;Nga et al, 2004); which has been an important region for emerging pathogens (Solomon et al, 2003). Wind-blown infected mosquitoes flying with air currents during the typhoon season supposedly played a role in the geographic expansion (Ritchie & Rochester, 2001).…”
Section: Origin and Genetic Diversity Of The Jevmentioning
confidence: 99%